MoRCiTO: hacia un modelo de referencia de ciberseguridad para la tecnología de la operación como preparación para la era cuántica, a fin de prevenir ataques de red a sistemas ciber-físicos en infraestructuras críticas - Amador-Donado, Siler; Pardo-Calvache, César-Jesús; Mazo-Peña, Raúl (Revista Científica, 2024)
This publication proposes a cybersecurity reference model for operation technology (MoRCiTO) as preparation for the quantum era to prevent network attacks on cyber-physical systems (CPS) in critical infrastructures (CI). The proposed model is the result of a review of primary studies that address different aspects such as, among others, the threats of quantum equipment against current cryptographic systems (as well as those that are yet to appear), enabling the characterization of the proposed reference model. This work contributes significantly to the field of cybersecurity, providing a reference model tailored to the imminent arrival of the quantum era. It is a crucial step towards CI preparedness against advanced threats and establishes a solid foundation for future research in quantum cybersecurity area. In addition, the model can be adopted by government entities and organizations in charge of CI management to strengthen their resilience against potential quantum attacks. Its implementation will help to ensure operational continuity and the protection of vital systems in a constantly evolving threat environment.